Rzeczy stają się sztuką-rzeczy tworzą sztukę. O zachowaniu upartych obiektów - Dietmar Rübel, Dietmar (Artium Quaestiones, 2019)
Translation into Polish of a text, originally published in German, by the German scholar Dietmar Rübel. He analyzes and theorizes issues related to materiality of an art work and art object in contemporary art. His account is an important voice in the recently topical debate in the humanities on the materiality or “thingness” of artworks, sometimes described as the “material turn”.